SARS-CoV-2 Vaccines: Status Report - Amanat, Fatima; Krammer, Florian (Immunity (Cambridge, Mass.), 2020)
SARS-CoV-2, the causal agent of COVID-19, first emerged in late 2019 in China. It has since infected more than 870,000 individuals and caused more than 43,000 deaths globally. Here, we discuss therapeutic and prophylactic interventions for SARS-CoV-2 with a focus on vaccine development and its challenges. Vaccines are being rapidly developed but will likely come too late to affect the first wave of a potential pandemic. Nevertheless, critical lessons can be learned for the development of vaccines against rapidly emerging viruses. Importantly, SARS-CoV-2 vaccines will be essential to reducing morbidity and mortality if the virus establishes itself in the population. Amanat and Krammer discuss therapeutic and prophylactic interventions for SARS-CoV-2, the causal agent of COVID-19, with a focus on vaccine development and its challenges.